The challenge of compassion in predator conservation - Simon Pooley; Simon Pooley (Frontiers in Psychology, 2022)
This paper argues that compassion for wild animals and the humans living alongside them should be integral to wildlife conservation. Nowhere is this more apparent than in predator conservation, and case studies are used to explore the consequences of wild animal attacks for human victims. Some arguments for extending compassionate consideration to animals seen as individuals are considered, along with the challenges these pose for predator conservation. A way forward from this apparent impasse is suggested, drawing on the capacity approach to embrace human with animal actors. The paper concludes with implications for predator conservation and recommendations, including incident responses sensitive to the traumatic impacts of attacks, and more collaborative approaches to handling human-wildlife interactions taking account of the capacities of local humans and wildlife.